Photogrammetric analysis of facial attractiveness in Malay Malaysian women - Miswan, Akmal Hisham (2019)
Background Asians are a heterogeneous group with different average and attractive facial features between individual ethnicities. This study aimed to establish normative anthropometric measurements of the Malay Malaysian Women's (MMW) face, compare results with the standard for North American White Women (NAWW), the neoclassical canons of facial proportions and other Asian ethnicities; and quantitatively defined aesthetic facial features in the MMW. Methods This is a cross-sectional photogrammetric study. In part 1 of this study, we obtained standardized frontal and lateral facial photographs of 103 MMW volunteers between the ages of 18 to 35. For each face, we measured 24 standard anthropometric parameters. We compared our results with the published NAWW norms and the facial canons proportions. In part 2 of the study, ten raters evaluated the photographs for aesthetics using a 10-point Likert’s scale. Attractive MMW (top 15%) were compared with the average MMW (remaining 85%), NAWW, and other ethnicities. Results The neoclassical facial canons were not found to apply to most of the MMW. We found significant differences between MMW and NAWW in 20 of 24 measurements (p<0.05). Attractive face in the MMW had a smaller total face height, smaller lower face height, and narrower mandible width compared to the average MMW. Comparing the normative and attractive MMW with other ethnicities indicated various interracial differences. Conclusion Grouping this patient into a single Asian category or using analysis standards used for whites are impractical. This study detailed comprehensive facial anthropometric data and aesthetic criteria for this population. The values presented here could be used as a standard for facial analysis in women of Malay descent.